2016
DOI: 10.4081/itjm.2016.643
|View full text |Cite
|
Sign up to set email alerts
|

The real life application of a procalcitonin-based algorithm to reduce antibiotic exposure in hospitalized patients with community acquired pneumonia: a proof of concept

Abstract: Community-acquired pneumonia (CAP) represents a common cause of hospitalization in Internal Medicine wards and a frequent cause of antibiotic prescription. An approach based on procalcitonin (PCT) algorithm, has shown to reduce the antibiotic exposure without affecting outcome, in patients admitted to hospital for pneumonia We conducted a study to evaluate the role of a PCT algorithm in a real-life perspective, to reduce the length of antibiotic treatment (AT) in patients hospitalized with CAP. We performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…In this paper they provide interesting data derived from real-world practice and combine appropriateness with attention to risks and costs of currently used therapies. 1 Although based on a smaller number of patients, their results confirm what larger experimental studies showed about the utility of PCT for diagnosis and management of respiratory tract infections. [2][3][4] Several papers published in recent years have shown that, in the presence of an opacity on chest X-ray, the negativity of PCT can reasonably exclude an underlying infectious bacterial cause.…”
supporting
confidence: 73%
“…In this paper they provide interesting data derived from real-world practice and combine appropriateness with attention to risks and costs of currently used therapies. 1 Although based on a smaller number of patients, their results confirm what larger experimental studies showed about the utility of PCT for diagnosis and management of respiratory tract infections. [2][3][4] Several papers published in recent years have shown that, in the presence of an opacity on chest X-ray, the negativity of PCT can reasonably exclude an underlying infectious bacterial cause.…”
supporting
confidence: 73%